The Juridical Position of Greek Minorities in Albania (European Journal of Interdisciplinary Studies, 2017)
Greek minority played an important role in the life and formation of the Albanian State. This minority has been concentrated mainly in the south of the country, more specifically in the border areas between Albania and Greece. The role of this minority has been important not only in the cultural development but also in the affirmation of the Albanian State. The Greek minority has been known legally as a national minority in 1921 when Albania was accepted in the League of Nations as a sovereign state with full rights. The admission to this international organisation was conditional upon the signing of a document in which Albania committed to recognise and guarantee full rights to minorities living in its territory. This document entitled "declaration on the protection of minorities in Albania" would force the Albanian State to submit detailed reports to the League of Nations about the situation of the minorities in the country. All minorities within the country lost their status after the end of the Second World War, during the Communist regime of Enver Hoxha. After the collapse of communism and the advent of democracy, minority rights were affirmed not only in the Albanian jurisdiction but also by several international agreements, such as the Convention of the Council of Europe for Protection of National Minorities. The actual judicial system in Albania guarantees national minorities equal rights with the Albanian population and, simultaneously, allows the preservation of their national identity.